2020
DOI: 10.32693/jgk.17.2.2019.602
|View full text |Cite
|
Sign up to set email alerts
|

Distribusi Spasial Foraminifera Di Perairan Teluk Cenderawasih, Papua Barat

Abstract: Sebanyak 20 sampel sedimen dari perairan Teluk Cenderawasih telah digunakan sebagai bahan studi foraminifera, yang bertujuan untuk mengetahui bagaimana sebaran spasial dan struktur komunitas foraminifera di perairan Teluk Cenderawasih. Hasil penelitian menunjukkan komposisi foraminifera planktonik yang terdiri dari 7 Genus dan 13 Spesies sedangkan foraminifera bentonik terdiri dari 57 Genus dan 87 Spesies. Foraminifera planktonik yang paling umum ditemukan karena muncul di seluruh sampel adalah genus Globigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several Anomalina globulosa, Hyalina balthica, and Rectobolivina that were deeper benthic species were also found in this layer (Table 3). [37] found Anomalina in Cendrawasih Bay at 700 m water depth, whereas Rectobolivina was spread out from 80 m to more than 100 m water depth in the El Salvador Sea [38].…”
Section: Foraminiferamentioning
confidence: 99%
“…Several Anomalina globulosa, Hyalina balthica, and Rectobolivina that were deeper benthic species were also found in this layer (Table 3). [37] found Anomalina in Cendrawasih Bay at 700 m water depth, whereas Rectobolivina was spread out from 80 m to more than 100 m water depth in the El Salvador Sea [38].…”
Section: Foraminiferamentioning
confidence: 99%
“…The detailed compilation of spatial data on planktonic foraminifera assemblages are available from sea surface sediments around the Indonesian Archipelago, including in the Simeulue sub-basin (Ding et al, 2006;Mohtadi et al, 2007Mohtadi et al, , 2009Natsir & Wibowo, 2019;Saputro et al, 2019;. A study by Ding et al (2006) showed that the characteristics of planktonic foraminifera groups in the western waters of Sumatra illustrate an oligotrophic environment with low salinity, a low gap in seasonal temperature, shallow thermocline, and high dissolution.…”
Section: Introductionmentioning
confidence: 99%